Analisis Diferensiasi Produk Berdasarkan Gaya Belajar Mahasiswa Pendidikan Teknologi Informasi FKIP Universitas Lampung - Sagala, Margaretha Karolina; Siregar, Erimson; Rinaldi, Daniel (Universitas Lampung, 2023)
Education serves as a means to shape an intelligent and character-driven generation, signifying its crucial role in creating and enhancing the quality of human resources. However, in reality, lecturers have not differentiated projects or products based on students' learning styles, be it visual, auditory, or kinesthetic. This indicates a lack of implementation of differentiated learning by the lecturers. This research aims to: (1) Analyze the teaching strategies applied by lecturers while teaching in the Information Technology Education Program (PTI); (2) Analyze the types of final projects or products given by lecturers during teaching in the PTI courses; (3) Analyze the factors causing lecturers not to provide projects or products based on students' learning styles. The research design is descriptive qualitative. The population consists of students in the Information Technology Education Program (PTI) at the Faculty of Teacher Training and Education (FKIP) at the University of Lampung. The sample for this study includes PTI students taking the Digital Circuit course in the Academic Year 2022-2023. To address the research questions, qualitative data were analyzed using descriptive statistics. Learning style test data were presented as frequencies and percentages. Data from interviews were then described. Findings from the learning style tests were triangulated with the interview data. Based on the conducted research, it is evident that students with a visual learning style tend to produce projects or products in the form of PowerPoint presentations or posters. On the other hand, students with an auditory learning style tend to create projects or products in the form of podcasts. In contrast, students with a kinesthetic learning style tend to generate projects or products in the form of videos. Kata kunci: Gaya Belajar, Pembelajaran Berdiferensiasi, Pendidikan Teknologi Informasi